European Stroke Organisation (ESO)- European Society for Minimally Invasive Neurological Therapy (ESMINT) guidelines on mechanical thrombectomy in acute ischemic stroke. (31st May 2019) - Turc, Guillaume; Bhogal, Pervinder; Fischer, Urs; Khatri, Pooja; Lobotesis, Kyriakos; Mazighi, Mikaël; Schellinger, Peter D; Toni, Danilo; de Vries, Joost; White, Philip; Fiehler, Jens
Abstract : Background: Mechanical thrombectomy (MT) has become the cornerstone of acute ischemic stroke management in patients with large vessel occlusion (LVO). The aim of this guideline document is to assist physicians in their clinical decisions with regard to MT. Methods: These guidelines were developed based on the standard operating procedure of the European Stroke Organisation, and followed the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. An interdisciplinary working group identified 15 relevant questions, performed systematic reviews and meta-analyses of the literature, assessed the quality of the available evidence, and wrote evidence based recommendations. Expert opinion was provided if not enough evidence was available to provide recommendations based on the GRADE approach. Results: We found high quality evidence to recommend MT plus best medical management (BMM, including intravenous thrombolysis whenever indicated) to improve functional outcome in patients with LVO related acute ischemic stroke within 6 hours after symptom onset. We found moderate quality of evidence to recommend MT plus BMM in the 6–24 hour time window in patients meeting the eligibility criteria of published randomized trials. These guidelines further detail aspects of prehospital management, patient selection based on clinical and imaging characteristics, and treatment modalities. Conclusions: MT is the standard of care in patients with LVO related acute stroke. Appropriate patient selection and timely reperfusion are crucial. Further randomized trials are needed to inform clinical decision making with regard to the mothership and drip-and-ship approaches, anesthaesia modalities during MT, and to determine whether MT is beneficial in patients with low stroke severity or large infarct volume.